RAMP-Accelerate Bootcamp | Venture Showcase Recording - CGIAR Accelerate For Impact Platform (2025)
Are you curious about the Selected Innovations for RAMP-Accelerate? Watch the recording of the Venture Showcase, the finale of the RAMP-Accelerate Bootcamp, which happened on Thursday, July 3, 2025, at the campus of the Alliance of Bioversity International and CIAT, in Palmira, Colombia.